PENGARUH KUALITAS PELAYANAN DAN PROMOSI TERHADAP CITRA PERUSAHAAN SERTA DAMPAKNYA PADA KEPUTUSAN NASABAH MENABUNG (Studi Kasus Pada Bank BRI Kantor Cabang Pembantu Meester) - Yolanda Yolanda; Dimas Firdaus (Jurnal Manajemen FE-UB, 2019)
This study aims to determine the extent of the Effect of Service Quality and Promotion onCompany Image and Its Impact on Savings Customer Decisions at Bank BRI Meester sub-branchoffice.The data used in this study were primary data collected from the results of respondents'answers based on the questionnaire given, as many as 97 people. Data processing method usesthe path analysis method (Path Analysis) with the help of SPSS version 23.0. Statistical testinguses partial significance test (T test) and simultaneous significant test (F test).The results showed that service quality has a direct effect on company image, promotionhas a direct effect on company image, service quality has a direct effect on customers' savingdecisions, promotions has a direct effect on customers' saving decisions, corporate image has adirect effect on customers' saving decisions, service quality has an indirect effect on thecustomer's decision to save through the company's image and promotion has an indirect effect onthe customer's decision to save through the company's image.Keywords: Service Quality, Promotion, Corporate Image, Customer Savings Decision